Enhanced bandwidth multi1ayer transducers for imaging applications - ZHANG, Q.; LEWIN, P.A. (Archives of Acoustics, 1995)
The operating frequency of the presently used PZT or PZT composite ultrasound imaging transducers is determined by the half wavelength resonance or fundamental thickness mode of vibration. This resonance frequency together with the two quarter wavelength matching layers governs the bandwidth of the transducer and hence control the overall resolution capabilities of the imaging system. This paper describes a new generation of multilayer ultrasound imaging transducers which are intentionally designed for off-resonance operation. The design makes use of the exceptionally wideband properties of the thin PVDF polymer film and offers excellent resolution. Moreover, such non-resonant design allows transducer to produce an image at virtually and clinically relevant frequency and can provide resolution tailored to clinician's needs. In addition, the design examined here offers pulse-echo sensitivity comparable to that achievable using PZT piezoceramic transducers. The design principle of the enhanced bandwidth transducer along with the transducer model specially developed to predict key electromechanical parameters of multilayer transducers is presented. These parameters include insertion loss, pulse-echo sensitivity, impulse response and electrical impedance. A few prototypes of this non-resonant tranducer design were built and tested. The experimental results were found to be in good agreement with those obtained from the computer simulations. Fundamental limitations of the design are pointed out and recommendations for future work are outlined.